Classical Solvability of a Free Boundary Problem for an Incompressible Viscous Fluid with a Surface Density Equation. (30th September 2013) - Kusaka, Yoshiaki
Abstract : We investigate a mathematical model introduced by Shikhmurzaev to remove singularities that arise when classical hydrodynamic models are applied to certain physical phenomena. The model is described as a free boundary problem consisting of the Navier-Stokes equations and a surface mass balance equation. We prove the local-in-time solvability in Hölder spaces.